2018
DOI: 10.1111/bju.14123
|View full text |Cite
|
Sign up to set email alerts
|

Nerve‐sparing radical cystectomy has a beneficial impact on urinary continence after orthotopic bladder substitution, which becomes even more apparent over time

Abstract: Nerve-sparing during RC and OBS was associated with better long-term continence outcomes. This becomes more apparent as the patients age with their OBS. We advocate a NS RC whenever an OBS is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 35 publications
2
57
0
Order By: Relevance
“…Pre‐operative continence and sexual function were poorly described. There were no pre‐operative incontinence and sexual dysfunction in 2 9,10 and 4 4,8,15,16 studies. Furthermore, participants of two included studies had comparative pre‐operative sexual function between NS and NNS group 9,10 …”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Pre‐operative continence and sexual function were poorly described. There were no pre‐operative incontinence and sexual dysfunction in 2 9,10 and 4 4,8,15,16 studies. Furthermore, participants of two included studies had comparative pre‐operative sexual function between NS and NNS group 9,10 …”
Section: Resultsmentioning
confidence: 86%
“…Age of included participants was comparable between the two groups in most of the studies, except for one article which included more younger participants in NS group 13 . As for tumor stage, most of the included studies were comparable between the two groups, only one had more favorable pathological T stage in NS group 8 . There was also no significant difference in post‐operative N stage compared with NNS group in three studies which reported this characteristic 4,8,14 (Table 2).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Increased nighttime diuresis and shift of free water into the concentrated urine may further attribute to incontinence. In a more recent study evaluating no vs unilateral vs bilateral nerve sparing, any degree of nerve sparing was associated with both day-and nighttime continence, which became even more apparent over time [7].…”
Section: Introductionmentioning
confidence: 93%